Особливості курирулуму початкової освіти Шотландії - Борисенко, Ірина (Studies in Comparative Education, 2013)
У статті проаналізовано ідеологію, ключові принципи конструювання та структуру курикулуму початкової освіти Шотландії, наведено приклади інновацій в оцінюванні навчальних досягнень учнів у початковій школі Шотландії. В статье анализируется идеология, ключевые принципы конструирования и структура курикулума начального образования Шотландии, приведены примеры инноваций в оценивании результатов учебной деятельности учащихся в начальной школе Шотландии. The curriculum in Scottish Primary schools is not determined by statute or regulation but by advice provided by the Government in non-statutory guidance. While England follows the National Curriculum, Scotland is currently implementing its own model, Curriculum for Excellence (CfE), a major educational reform aimed at providing a wider, more flexible range of subjects and courses for children and young people aged 3 to 18. The changes brought about by Curriculum for Excellence should lead to improved quality of learning and teaching and increased attainment and achievement for all children and young people in Scotland, including those who need additional support in their learning CfE focuses on developing four key capacities in pupils, helping them to become: successful learners, confident individuals, responsible citizens, effective contributors. The curriculum is designed on the basis of the following principles: challenge and enjoyment; breadth; progression; depth; personalization and choice; coherence; relevance. The Curriculum for Excellence is defined broadly to include all the activities which contribute to the development and achievements of children at all stages in their schooling. These include the ethos and life of the school as a community; curriculum areas and subjects; interdisciplinary projects; and opportunities for personal achievements. There also opportunities to develop skills for life and skills for work, with a focus on literacy, numeracy and well-being across the curriculum. All learning in the Curriculum for excellence is described in terms of experience and outcomes which describes the expectation for learning and progression in all areas of the curriculum. The experiences and outcomes are grouped into five levels – early (in which most children will undertake learning to the end of P1); first (in which most children will undertake learning by the end of P4); second (in which most children will undertake learning by the end of P7); and fourth. The aim of the curriculum for Excellence is to help prepare all young people in Scotland to take their place in a modern society and economy. The curriculum will provide a framework for all young people in Scotland to gain the knowledge and skills for learning, skills for life and skills for work that they need.